The Influence of Principal Leadership on the Performance of Elementary School Teachers in Ngawen District, Klaten Regency - Henry Fisca Englishtya; Rejokirono; Rahmat Mulyono (Universitas Pakuan, 2026)
Teacher performance serves as the primary benchmark in advancing the quality of basic education. However, the 2025 Education Report Card recorded that 34.48% of elementary schools in Ngawen District had inadequate learning quality. This fact was reinforced by supervision results showing that 53% of teachers had not completed administrative requirements, and 65% had not varied their teaching methods. These conditions are assumed to occur due to the less-than-optimal leadership of principals in providing supervision, motivation, and innovation. Therefore, this study was conducted to analyze the extent of the influence of principal leadership on the performance of elementary school teachers in the Ngawen District, Klaten. Using a quantitative approach with a survey method, the sample was selected through proportional random sampling techniques. Based on the results of questionnaire data analysis using simple linear regression, it was concluded that there is a positive and significant influence between principal leadership and teacher performance. This means that the better the level of leadership, the higher the teacher performance. This study once again highlights the importance of the principal’s role as a supervisor, innovator, and motivator for teachers..